Video Streaming Implementation for Open Source Based Online Learning : - Ansari, Muhammad; Setiawan, Bayu Elpan (Jurnal Manajemen Informatika Medicom (JMI), 2023)
The very rapid development of information and communication technology encourages various users, institutions and agencies to utilize video learning systems or video tutorials as learning media to increase the effectiveness and flexibility of learning. The advantages that can be obtained with video learning are in terms of flexibility and mobility. Through video learning learning material or video tutorials can be accessed anytime and from anywhere and the material can be enriched with various learning resources. Through video-learning, tutors or instructors can make their own video tutorials as learning materials for students or employees which can be accessed directly via their own server or website so they can add more value to their practice. The results of implementing video streaming for Online Learning using the Linux Ubuntu Server operating system and the Ostube application with internet network infrastructure using TelkomSpeedy Internet Service Provider (ISP) with a bandwidth of 1 Mbps obtained the results of measuring the delay parameter with an average delay value of 6.6 ms so that it can be concluded that it is included in the very good category. The results of measuring the packet loss parameter obtained an average packet loss value of 0%, which is included in the Tiphon version of the very good category. For the measurement of Throughput values ​​obtained an average value of 3987 kbit/sec. While measuring the peak jitter value, the average value of jitter time is 2,909 ms. From the calculation of the jitter value, the category of jitter degradation according to Tiphon's version is very good. 6 ms so that it can be concluded that it is in the very good category..